Über die Grenzwertsätze für grosse Abweichungen - Aleškevičienė, A. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Алешкявичене. О предельных теоремах для больших уклонений A. Aleškevičienė. Apie ribines teoremas dideliems atsilenkimams